Optimasi pengelolaan permintaan dan persediaan dengan pendekatan vehicle routing problem pada PT. XYZ - Afrizal, Fikri; Pratiwi, Annisa Indah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Company PT. XYZ, which operates in the agro-industrial sector, especially processing cane sugar, is currently facing problems in managing product demand and supply. The traditional methods used by companies often cause a mismatch between available stock and market demand, resulting in increased operational costs and disruption in the distribution process. This research proposes the application of the Vehicle Routing Problem (VRP) and Inventory Routing Problem (IRP) models as a solution to overcome this problem. By optimizing distribution routes and managing inventory more efficiently, PT. XYZ is expected to improve its supply chain performance, reduce costs, and increase customer satisfaction. However, implementing this model requires quite large investments and good data quality. Therefore, companies need to carry out careful and gradual planning in implementing this solution.